Immittance Response on Carboxymethyl Cellulose Blend with Polyvinyl Alcohol- Doped Ammonium Bromide-Based Biopolymer Electrolyte - Mazuki, Norfatihah; Nagao, Yuki; Samsudin, Ahmad Salihin (UI Scholars Hub, 2018)
The blended carboxymethyl cellulose (CMC) and polyvinyl alcohol (PVA) doped with various compositions of ammonium bromide (NH4Br)-based solid biopolymer electrolytes (SBEs) were prepared by using the casting method. In this present work, CMC/PVA–NH4Br SBE thin film was used to investigate the electrical conductivity via electrical impedance spectroscopy. The maximum conductivity obtained was 3.21 X 10−4 S cm−1 for sample AB20 at ambient temperature (303 K), and this result might be due to the increased number of charge carrier. A dielectric study was conducted to understand the conductivity behavior. The electrical properties have been measured as a function of frequency of ɛr, ɛi, Mr, and Mi, indicating a non-Debye type behavior.